Facile fabrication of LaFeO3/zeolite composite for degradation of tetracycline with enhanced photo‐Fenton catalytic activity under visible light. Issue 1 (17th February 2022) - Nga, Phan Thi To; Nhan, Phan Chi; Huyen, Tran Thi Thanh; ,
Abstract: LaFeO3 /zeolite (LFO‐Z) composite has been successfully synthesized via impregnation‐calcination method for the photo‐Fenton degradation of Tetracycline (TC). The incorporation of LaFeO3 particles on zeolite support contributes to the enhancement in photo‐Fenton catalytic activity of LFO‐Z photocatalyst by increasing the contact area between the material and TC molecules. The LFO‐Z photocatalyst was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X‐ray diffraction (XRD), N2 adsorption‐desorption, and optical absorption spectra. Different operational parameters such as catalyst dosage, H2 O2 concentration, pH was investigated in the photo‐Fenton catalytic degradation of TC. 76.4 % of TC was degraded after 150 min exposure to visible light under the conditions of 1 g L ‐1 LFO‐Z, 10 mg L ‐1 TC, 10 mM H2 O2 and pH of 6. The LFO‐Z composite shows a high stability and reusability, suggesting its potential use as a photocatalyst for pharmaceutical degradation via the photo‐Fenton process.